2010
DOI: 10.1111/j.1745-4565.2010.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

ELECTRON BEAM IRRADIATION ON NALIDIXIC ACID‐RESISTANT SALMONELLA MONTEVIDEO IN COOKED TOMATO PUREE OF VARIOUS pH VALUES

Abstract: Electron beam (e‐beam) is a technology that uses ionizing radiation to destroy bacteria in a nonthermal manner. D10 values were obtained for nalidixic acid (NA)‐resistant Salmonella Montevideo in autoclaved Roma tomato puree pH adjusted to pH 3.4, 3.9, 4.4 and 4.9 and subjected to e‐beam at 0 (control), 0.5, 1.0, 1.5, 2.0 and 2.5 kGy. Survivors were enumerated using standard spread‐plating method. NA‐resistant S. Montevideo was not recovered in puree at pH 3.4 or 3.9. Significant reductions (P < 0.05) were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…James, Jaczynski, and Matak (2010) determined the antimicrobial efficacy of e-beam against acid-resistant S. Montevideo in tomatoes with varying acidity. Tomatoes were subjected to e-beam at 0 (control), 0.5, 1.0, 1.5, 2.0 and 2.5 kGy.…”
Section: Microbial Inactivation Kinetics and Process Calculationsmentioning
confidence: 99%
“…James, Jaczynski, and Matak (2010) determined the antimicrobial efficacy of e-beam against acid-resistant S. Montevideo in tomatoes with varying acidity. Tomatoes were subjected to e-beam at 0 (control), 0.5, 1.0, 1.5, 2.0 and 2.5 kGy.…”
Section: Microbial Inactivation Kinetics and Process Calculationsmentioning
confidence: 99%
“…Ionising radiation effectively inactivates microorganisms including foodborne pathogens (Farkas 1998, Black and Jaczynski 2006, 2007, Chalise et al 2007, O'Bryan et al 2008, Arvanitoyannis et al 2009, Arvanitoyannis and Stratakos 2010, James et al 2010. Therefore, application of ionising radiation to food processing enables food manufacturers to increase microbial food safety and extend shelf-life of food products.…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that Salmonella contaminates the surface of vegetables and enters into the edible parts of different varieties of plants like lettuce, tomatoes, radish sprouts, bean sprouts, and barley (Tahergorabi et al, 2012). James et al (2010) studied the effect of e-beam on S. Montevideo inactivation in tomatoes. They observed significant reductions in the number of microorganisms subjected to >1.5 kGy irradiation.…”
Section: Applications Of Ionizing Irradiationmentioning
confidence: 99%